FACTORS RELATED TO K4 ANTENATAL CARE VISITS IN THE WORKING AREA OF BERNUNG PUBLIC HEALTH CENTER IN PESAWARAN REGENCY - Melinda, Novia; Primadevi, Inggit; Isnaini, Maulia; Fauziah, Nur Alfi (Universitas Aisyah Pringsewu, 2024)
The Indonesian Ministry of Health's family health program figures show an annual rise in the number of maternal deaths. Pregnancy is one of the factors contributing to Indonesia's high rate of maternal death, specifically because high-risk pregnancies are caused when pregnant women do not use Antenatal Care (ANC), which prevents health professionals from detecting pregnancy-related issues. According to the Lampung Province's 2022 SSGI, Pesawaran Regency has the lowest prenatal care coverage (85.70% K4 coverage) out of the 15 regencies/cities. The research objective was to determine the factors associated with K4 visits in the working area of Bernung Public Health Center in Pesawaran Regency. This research design is quantitative with a cross-sectional approach. The population and sample in this study were all third-trimester pregnant women in the working area of Bernung Public Health Center, Pesawaran Regency, totaling 65 pregnant women. Data collection used primary and secondary data with questionnaire instruments and MCH books. Bivariate analysis in this study used the eta correlation test.The research result showed that there was a correlation between education and K4 antenatal care visits (p-value 0.793) and there was no correlation between job (p-value 0.104), distance (p-value 0.621), and knowledge (p-value 0.444) with K4 antenatal care visits. In order for moms to know the status of their pregnancy and identify any high risk of pregnancy early on, it is advised that expectant mothers always take care of their pregnancy by routinely using antenatal care services